2020
DOI: 10.1037/dev0000889
|View full text |Cite
|
Sign up to set email alerts
|

Causality influences children’s and adults’ experience of temporal order.

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…However, the work of Blakey et al (2019) suggests that even preschoolers’ time perception is susceptible to influence from their causal representations. Moreover, Tecwyn et al (2020) have demonstrated that the causal representations of 4- to 10-year-old children influence their judgements about the temporal order of events in a similar way to adults. That is, children reorder events to align with their causal beliefs in the same way as adults do ( Bechlivanidis & Lagnado, 2013 , 2016 ).…”
Section: Developmental Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the work of Blakey et al (2019) suggests that even preschoolers’ time perception is susceptible to influence from their causal representations. Moreover, Tecwyn et al (2020) have demonstrated that the causal representations of 4- to 10-year-old children influence their judgements about the temporal order of events in a similar way to adults. That is, children reorder events to align with their causal beliefs in the same way as adults do ( Bechlivanidis & Lagnado, 2013 , 2016 ).…”
Section: Developmental Predictionsmentioning
confidence: 99%
“…The relation between time and causality in adults is bidirectional: not only is temporal information used when making causal inferences (e.g., Bramley et al, 2018 ; Shanks, Pearson & Dickinson, 1989 ), but causal representations influence the perception of both the temporal order of and temporal interval between events ( Bechlivanidis & Lagnado, 2013 , 2016 ; Buehner, 2012 , 2015 ; Haggard et al, 2002 ; Tecwyn et al, 2020 ). The perception of a cause and its direct effect as temporally closer than two causally unrelated events is known as temporal binding , and it is this phenomenon, and specifically its developmental profile, that is the focus of the current study.…”
mentioning
confidence: 99%
“…Do you think that you would spot such a weird succession of events? Previous research indicates that you probably would not (Bechlivanidis & Lagnado, 2013, 2016Tecwyn et al, 2020). Well, maybe you were not paying attention, or perhaps the scene was too weird to be remembered accurately.…”
Section: Research Articlementioning
confidence: 99%
“…When the timing of stimulus presentations is manipulated to occur closely before and after saccadic eye movements, their order is reversed (Kresevic et al, 2016;Morrone et al, 2005). More relevant to the current purposes, it has been shown that when presented with stimuli that give the impression of a recently learned (Bechlivanidis & Lagnado, 2013) or a familiar (Bechlivanidis & Lagnado, 2016) causal relationship that nevertheless violates the expected temporal order, adults and children as young as 4 years old (Tecwyn et al, 2020) report having seen the causal instead of the objective temporal order of events.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation